Prevalence of HIV/STIs and correlates with municipal characteristics among female sex workers in 13 Mexican cities - Thomas L Patterson; Steffanie A Strathdee; Shirley J Semple; Claudia V Chavarin; Daniela Abramovitz; Tommi L Gaines; Doroteo Mendoza; Hugo Staines; Gregory A Aarons; Carlos Magis-Rodríguez (Salud Pública de México, 2019)
Objective. To identify correlates of HIV/STI prevalence among 13 cities with varying sizes of female sex worker (FSW) populations and municipal characteristics in Mexico. Materials and methods. FSWs underwent interviews and testing for HIV, syphilis, gonorrhea and chlamydia. Logistic regression explored variations in HIV/STI prevalence. Results. Among FSWs (n=1 092), prevalence across 13 sites was: HIV: 0.4% (range: 0%-1.4%): syphilis: 7.8% (range: 0%-17.2%); chlamydia: 15.3% (range: 5.7%-32.2%); gonorrhea: 2.9% (range 0%-13.8%), and any HIV/STI: 23% (range: 9.9%- 46%). Municipalities with high human development scores and a lower municipal marginalization index had higher odds of combined HIV/STI prevalence. After controlling for site-specific variability in municipal characteristics, greater risk of HIV/STIs was associated with lower education, having a spouse diagnosed or treated for an STI, unaffordability of condoms, and having non-Mexican clients. Conclusions. Prevalence of HIV/STIs varies across Mexican municipalities indicating the need for surveillance to identify hotspots for targeted resource allocation.